PROTOTYPE JEMURAN PAKAIAN OTOMATIS MENGGUNAKAN MIKROKONTROLLER - Sandi Nurhadiyanto; Bekti Yulianti (JURNAL TEKNOLOGI INDUSTRI, 2019)
Armed with previous tools regarding pre-existing automatic clothespins. Where the shortcomings of this tool are the absence of assistance to dry clothes when the clothesline is entered (not in the position of not drying), so that the activity of drying the tools is not optimal.The components are selected in order to match the characteristics and specifications of the selected components with the needs of the tool so that the tools that are made can work properly, light sensors and raindrop sensors in this simulator for reasons of convenience and safety.The speed of light is 299,752,458 meters per second so that the checking conditions for the value of light intensity can vary (uncertain). Therefore, the position for placing the LDR must be considered.Keyword : Mikrocontroller, LCD, LED, Motor DC